2014
DOI: 10.1116/1.4876736
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological investigation of an antibacterial sandwich layer system

Abstract: To allow medical application of an artificial bladder made of biocompatible polyurethane, a long-term stable antibacterial coating is required. Alone, the artificial bladder exhibits no defense against microorganisms. Silver coating provides long-term antibacterial protection by the continuous release of silver ions into aqueous solutions. To control and to prolong the rate of silver ion release, the deposited silver film has to be protected by an inert film of biocompatible polyparylene by means of chemical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…After 3 min of plasma exposure, the contact angle H significantly decreased from 84. 18 to 29.68 , confirming the increased hydrophilicity caused by the formation of polar oxygen-containing groups and not by the changes in roughness. Bi et al have shown by x-ray photoelectronic spectroscopy that O 2 treatment of PPX under similar exposure conditions causes the origin of two new peaks at 287.8 and 289.3 eV in the deconvoluted C 1s spectrum, which they attributed to the carbon atoms in the free carbonyl group (C¼O) and carbonate group (O 2 C¼O), respectively.…”
Section: B Increased Wettability Of Ppx-n After Plasma Treatmentsupporting
confidence: 57%
See 1 more Smart Citation
“…After 3 min of plasma exposure, the contact angle H significantly decreased from 84. 18 to 29.68 , confirming the increased hydrophilicity caused by the formation of polar oxygen-containing groups and not by the changes in roughness. Bi et al have shown by x-ray photoelectronic spectroscopy that O 2 treatment of PPX under similar exposure conditions causes the origin of two new peaks at 287.8 and 289.3 eV in the deconvoluted C 1s spectrum, which they attributed to the carbon atoms in the free carbonyl group (C¼O) and carbonate group (O 2 C¼O), respectively.…”
Section: B Increased Wettability Of Ppx-n After Plasma Treatmentsupporting
confidence: 57%
“…To improve adhesion of silver nanoparticles to the surface, catheters were coated with poly(p-xylylene) or parylene (PPX-N), a biocompatible polymer. 18 In a previous work, we have already optimized the silver thickness to compare PPX-N and silver particle morphology and tested minimum inhibitory concentration of silver ions in synthetic urine against E. coli and S. cohnii. 19 The aim of this study is to evaluate the antibacterial efficacy of silver/PPX catheters in a simulated body fluid (synthetic urine), including the power to prevent generation of a biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…With these measurements, it could be shown that the desired thickness of the cap layer is between 150 and 300 nm [ 40 ], which, in turn, determines the upper limit for the thickness of the silver depot. In fact, the mean value of 50 μg/L or 0.45 μmol/L corresponds exactly to the results, which are possible in an environment that is determined by the presence of Cl − , but also of urea and urease.…”
Section: Resultsmentioning
confidence: 99%
“…Among the physical and chemical standard methods to detect traces are inductively coupled plasma optical emission spectroscopy (ICP-OES), cyclic voltammetry, and atomic absorption spectroscopy (AAS). The former two methods have been extensively used and are described in [ 19 , 40 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation